Biosynthesis of α-solanine and α-chaconine in potato leaves (Solanum tuberosum L.) – A 13CO2 study. (15th December 2021) - Baur, Sebastian; Frank, Oliver; Hausladen, Hans; Hückelhoven, Ralph; Hofmann, Thomas; Eisenreich, Wolfgang; Dawid, Corinna
Highlights: A 13 CO2 pulse-chase experiment reveals the biosynthetic history of α -solanine and α -chaconine, the two major steroidal glycoalkaloids in potato. The detection of 13 C2 -units in the steroidal moieties of the SGAs demonstrate the origin of isopentenyl diphosphate and dimethylallyl diphosphate precursors from the mevalonate pathway. The specific labelling patterns in the SGAs reflect the regio- and stereochemistry in cyclization of the 2, 3-oxidosqualene precursor. The partitioning of 13 C2 -pairs in the F-rings indicates a non-stereoselective hydroxylation of the terminal methyl groups in the side chain of the sterol precursor leading to a mixture of 25 S - and 25 R -epimers of SGAs. Abstract: α -Solanine and α -chaconine are the major glycoalkaloids (SGAs) in potatoes, but up to now the biosynthesis of these saponins is not fully understood. In planta 13 CO2 labeling experiments monitored by nuclear magnetic resonance spectroscopy (NMR) and high-resolution mass spectrometry (HRMS) unraveled the SGA biosynthetic pathways from CO2 photosynthates via early precursors to the SGAs. After a pulse of ~ 700 ppm 13 CO2 for four hours, followed by a chase period for seven days, specific 13 C-distributions were detected in SGAs from the leaves of the labeled plant. NMR analysis determined the positional 13 C-enrichments in α -solanine and α -chaconine characterized by 13 C2 –pairs in their aglycones. These patterns were in perfect agreement with a mevalonate-dependent biosynthesis of the isopentenyl diphosphate and dimethylallyl diphosphate precursors. The 13 C-distributions also suggested cyclization of the 2, 3-oxidosqualene precursor into the solanidine aglycone backbone involving a non–stereoselective hydroxylation step of the sterol a mixture of 25 S -/25 R -epimers of the SGAs.